ANALISIS POLA RUANG DAN TIPOLOGI ARSITEKTUR MARITIM DI PESISIR PANTAI LEATO SELATAN KOTA GORONTALO - Mohammad Imran; Putalan, Reinal; Hakim, Didiet Haryadi; Bahmid, Mohamad Raihan; Isima, Mohamad Teguh (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Coastal areas are strategic regions that reflect the interaction between humans and the maritime environment. In Leato Selatan Village, Gorontalo City, there is a coastal community settlement with distinctive spatial characteristics and architectural forms as a result of adaptation to local geographical and cultural conditions. This study aims to analyze the spatial patterns of the settlement and the maritime architectural typology in the area. The method used in this study is a descriptive qualitative approach with data collection techniques through field observations, in-depth interviews, visual documentation, and literature studies. The analysis was conducted on the spatial arrangement, building orientation, and architectural elements that reflect adaptation to the coastal environment. The results of this study identified the spatial patterns in South Leato Village as coastal fishing settlements and classified the maritime architectural typology that reflects local wisdom and socio-ecological factors in South Leato Village.